Quantitative Gastrointestinal and Psychological Traits Associated with Obesity and Response to Weight-loss Therapy - Acosta, Andres (Gastroenterology, 2014)
BACKGROUND & AIMS: Weight loss following pharmacotherapy varies greatly. We aimed to examine associations of quantitative gastrointestinal and psychological traits with obesity, and to validate the ability of these traits to predict responses of obese individuals to pharmacotherapy. METHODS: In a prospective study, we measured gastric emptying (GE) of solids and liquids, fasting and postprandial gastric volume, satiation by nutrient drink test (volume to fullness and maximal tolerated volume), satiety following an ad-libitum buffet meal, gastrointestinal hormones, and psychological traits in 328 normal weight, overweight, or obese adults. We also analyzed data from 181 previously studied adults to assess associations between a subset of traits with body mass index and waist circumference. Latent dimensions associated with overweight or obesity were appraised by principal component analyses. We performed a proof-of-concept, placebo-controlled trial of extended-release phentermine and topiramate in 24 patients, to validate associations between quantitative traits and response to weight-loss therapy. RESULTS: In the prospective study, obesity was associated with fasting gastric volume (P=.03), accelerated GE (P<.001 for solids and P=.011 for liquids), lower postprandial levels of peptide tyrosine tyrosine (P=.003), and higher postprandial levels of glucagon-like peptide 1 (P<.001). In a combined analysis of data from all studies, obesity was associated with higher volume to fullness (n=509; P=.038) and satiety with abnormal waist circumference (n=271; P=.016). Principal component analysis identified latent dimensions that accounted for ∼81% of the variation among overweight and obese subjects, including satiety or satiation (21%), gastric motility (14%), psychological factors (13%), and gastric sensorimotor factors (11%). The combination of phentermine and topiramate caused significant weight loss, slowed GE, and decreased calorie intake; weight loss in response to phentermine and topiramate was significantly associated with calorie intake at the prior satiety test. CONCLUSION: Quantitative traits are associated with high body mass index; they can distinguish obesity phenotypes and, in a proof-of-concept clinical trial, predicted response to pharmacotherapy for obesity.